“Let me hear Thy voice”: Michèle Roberts’s Refiguring of Mary Magdalene in the Light of The Song of Songs - Filipczak, Dorota (The Woman Artist: Essays in memory of Dorota Filipczak, 2024)
The article engages with the protagonist of The Secret Gospel of Mary Magdalene by Michèle Roberts, first published in 1984 as The Wild Girl. Filipczak discusses scholarly publications that analyze the role of Mary Magdalene, and redeem her from the sexist bias which reduced her to a repentant whore despite the lack of evidence for this in the Gospels. The very same analyses demonstrate that the role of Mary Magdalene as Christ’s first apostle silenced by patriarchal tradition was unique. While Roberts draws on the composite character of Mary Magdalene embedded in the traditional association between women, sexuality and sin, she also moves far beyond this, by reclaiming the female imaginary as an important part of human connection to the divine. At the same time, Roberts recovers the conjunction between sexuality and spirituality by framing the relationship of Christ and Mary Magdalene with The Song of Songs, which provides the abject saint from Catholic tradition with an entirely different legacy of autonomy and expression of female desire, be it sexual, maternal or spiritual. The intertext connected with The Song of Songs runs consistently through The Secret Gospel of Mary Magdalene. This, in turn, sensitizes the readers to the traces of the Song in the Gospels, which never quote from it, but they rely heavily on the association between Christ and the Bridegroom, while John 20 shows the encounter between the risen Christ and Mary Magdalene in the garden whose imagery is strongly suggestive of the nuptial meeting in The Song of Songs.